Analysis of Open Loop V/F Control of Three Level Cascaded H- Bridge Inverter Fed Induction Motor Drive - Patel, Chirag T; Bhati, Jignesh B (International Journal of Computer Sciences and Engineering, 2018)
Open loop V/f control of cascaded H-Bridge inverter fed induction motor drive is simulated in PSIM environment. Cascaded H-Bridge three level inverter is used to obtain good quality of output voltage. This method can be implemented by change in the supply voltage and frequency applied to the three phase induction motor at constant ratio. . The proposed system is an effective replacement for the conventional method which produces high switching losses. Phase shifted SPWM control scheme has been used for Cascaded H-Bridge multilevel inverter. Simulation results are presented in this paper to validate the effectiveness of the proposed scheme.